ESTIMASI BIOMASA DAN KARBON TERSIMPAN PADA Pinus merkusii Jungh. & de Vriese DI HUTAN PINUS GN. BUNDER, TN. GN. HALIMUN SALAK - Ruddy Polosakan; Laode Alhamd; Joeni S. Rahajoe (Research Center for Biology-Indonesian Institute of Sciences, 2014)
A study on the biomass and carbon stock estimation of Pinus merkusii Jungh. & de Vriese plantation has been conducted on 17-years and 30-years old pine forest in Gunung Bunder, Halimun Salak National Park. The method used was the allometric with non destructive technique. The results showed that pine trees density of 30-years old pine was 542 trees ha-1 ; the basal area (BA) was 26.8 m2 ha-1; trees density of 17-years old pine was 1,398 tree ha-1 with BA was 36.2 m2 ha-1. The estimation of biomass, carbon sinks and CO2 sequestration of 30-years old pine were 203.7, 96.5 and 354.2 ton ha-1, respectively. Meanwhile, the estimation of biomass, carbon sinks and CO2 sequestration of 17-years old pine were 188.3, 86.8 and 318.5 ton ha-1, respectively. Value of the environmental services derived from the CO2 absorption for the development of a pine forest ranged from US. 1,847.09 to 2,054.22, at two ages of pine trees.